Multiple Weyl and double-Weyl points in the phonon dispersion of P4332 BaSi2 - Li, Yang (Frontiers in Physics, 2023)
Weyl semimetals, classified as solid-state crystals and whose Fermi energy is accurately situated at Weyl points (WPs), have received much attention in condensed matter physics over the past ten years. Weyl quasiparticles have been observed in the electronic and bosonic regimes, in addition to the extensive amount of theoretical and numerical predictions for the Weyl semimetals. This study demonstrates that 12 single Weyl phonons with linear dispersion and six double Weyl phonons with quadratic dispersion coexist between two specific phonon branches in real material P4332 BaSi2. The 12 single Weyl phonons and the six double Weyl phonons can form a Weyl complex phonon, which hosts a zero net chirality.